Fiddler Crabs (Crustacea: Decapoda: Ocypodidae) From Coastal Ecuador and the Galápagos Islands: Species Descriptions and DNA Barcodes - Carl L. Thurman; John C. McNamara; Hsi‐Te Shih; Mariana V. Capparelli (Ecology and Evolution)
ABSTRACT Neotropical regions near the equator are recognized as speciation “hot spots” reflecting their abundant biodiversity. In western South America, the coasts of Panama, Colombia, Ecuador, the Galápagos Archipelago, and northern Peru form the Tropical Eastern Pacific biome. This area has the greatest heterogeneity of sympatric fiddler crab species of any portion of the planet. Since the coastal fauna has not been assessed for almost 50 years, we studied fiddler crab species diversity in Ecuador and on the Galápagos Archipelago. Preserved collecting records for various species were examined at the U.S. National Museum of Natural History, Washington, DC, the American Museum of Natural History, New York, and the Naturalis Biodiversity Center, Leiden, the Netherlands. During a field study, 51 locations were collected resulting in over 870 preserved specimens (120 lots) along the 2237‐km (1390 mi) coast of Ecuador and on three Galápagos Islands. A neighbor‐joining tree was constructed using the Kimura 2‐parameter model with a partial DNA sequence of the cytochrome oxidase‐subunit 1 gene (COI) for a barcoding study. Twenty‐five taxa were collected during the surveys, while two more were noted from the literature and museum collections. Five published species are new to Ecuador. The species assemblage was divided among four genera: Uca, Leptuca, Minuca, and Petruca. Morphological definitions and photographic images are given for 27 species. COI sequences were obtained for 27 operational taxonomic units from Ecuador, with three morphologically indistinguishable cryptic or pseudocryptic taxa also revealed. Based on species distributions, it appears that the area between Cabo San Lorenzo and Punta Santa Elena serves as a weak barrier separating some “northern” from “southern” taxa. Since coastal Ecuador is undergoing rapid economic development, the construction of maricultural facilities and the deforestation of mangroves promote wholesale habitat destruction. As habitat diversity is reduced, it is expected that there will be, in general, a local decline in fiddler crab species diversity with some taxa becoming rare or extinct.